2022
DOI: 10.3390/polym14102053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Temperature Hydrothermal Treatment on the Cellulose Derived from the Buxus Plant

Abstract: Cellulose has attracted considerable attention as the most promising potential candidate raw material for the production of bio-based polymeric materials. In the last decade, significant progress has been made in the production of biopolymers based on different cellulose forms. In this study, cellulose was obtained in an innovative and environmentally friendly way, using boxwood powder. Crude cellulose was obtained by treating Buxus powder with an ethanol–acetic acid–water mixture. Refined cellulose was then o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Sphingans have also been selected for many applications because of their thermal stability due to their ability to covalently cross-link, high M W , and stable glycosidic bonds. 3436 Both TGA and DSC were conducted to establish the thermal properties of this novel material and to enable comparison to fellow sphingans. The results of TGA show that weight loss occurs in two stages.…”
Section: Resultsmentioning
confidence: 99%
“…Sphingans have also been selected for many applications because of their thermal stability due to their ability to covalently cross-link, high M W , and stable glycosidic bonds. 3436 Both TGA and DSC were conducted to establish the thermal properties of this novel material and to enable comparison to fellow sphingans. The results of TGA show that weight loss occurs in two stages.…”
Section: Resultsmentioning
confidence: 99%
“…When the pyrolysis conditions were reached, cellulose would be pyrolyzed into cellulose triglycan, bioglycan, and levoglucose glycan [92] . As shown in Table 1, the cellulose generally showed an increase in the degree of crystallinity [74–78] and a decrease in the degree of polymerization [74–76] . This change contributed to obtaining a cellulose solution in mild mediums and preparing cellulose‐based hydrogel with better mechanical properties.…”
Section: Modification Of Cellulosementioning
confidence: 99%
“…It is noted that, in the experimental process of cellulose hydrolysis, cellulose reaches the maximum temperature at the reactor inlet where the supercritical water is mixed with the cellulose. Thus, the dehydration reaction can be accelerated with the enhancement of the thermal properties [26]. In this study, the cellulose mass concentration at the reactor inlet is selected as the same as that reported in a recent experimental study [27].…”
Section: Statement Of the Problem And Solutionmentioning
confidence: 99%
“…The computational results are compared with those in the literature [23]. Though quite a few experimental studies have been reported in the literature for cellulose hydrolysis [6,26,27], detailed kinetic modeling of the hydrolysis process is still lacking. The present study can contribute to the rational understanding of cellulose hydrolysis for better, controllable production of cellulose-derived biofuels and other value-added chemicals, especially, beneficial to predict the yield of cellulose derivatives, e.g., glucose, fructose, 5-HMF, glyceraldehyde, erythrose, glycolaldehyde, aldose, threose, and others.…”
Section: Introductionmentioning
confidence: 99%